2003
DOI: 10.1159/000069939
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Lesion Size on the Diagnostic Performance of Dermoscopy in Melanoma Detection

Abstract: Background: Dermoscopy is able to correctly classify a higher number of melanomas than naked-eye examination. Little is known however about factors which may influence the diagnostic performance during practice. The aim of the study was to analyze the effect of size of the lesion on diagnostic performance of dermoscopy in melanoma detection. Methods: Eight dermatologists examined clinical and, separately, clinical and dermoscopic (combined examination) images of 200 melanocytic lesions previously excised [64 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
34
2

Year Published

2005
2005
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(38 citation statements)
references
References 7 publications
2
34
2
Order By: Relevance
“…5 This seems to be in agreement with the present study, in which only 1 out of 76 suspicious lesions was diagnosed as malignant. Ordinary benign melanocytic lesions usually are not clinically suspicious.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…5 This seems to be in agreement with the present study, in which only 1 out of 76 suspicious lesions was diagnosed as malignant. Ordinary benign melanocytic lesions usually are not clinically suspicious.…”
Section: Discussionsupporting
confidence: 93%
“…1,2 However, the diagnostic accuracy of dermoscopy significantly depends on the degree of experience of the examiners and size of lesions. 3-5 Small melanocytic lesions remain a significant diagnostic challenge not only for clinicians and dermoscopists, but also for pathologists because progressive smaller lesions are excised under the screening of dermoscopic features. This study aims to evaluate the range of possible histopathological diagnoses in a group of melanocytic lesions up to 6 mm considered suspicious for MM on clinical and dermoscopical examination.…”
Section: Introductionmentioning
confidence: 99%
“…One study even noted a 10% drop in the sensitivity for detecting melanoma when used by untrained dermatologists [73]. Furthermore, it is unclear whether dermoscopy has added value for melanomas smaller than 6 mm [74][75][76].…”
Section: Additional Diagnostic Tools Dermoscopymentioning
confidence: 99%
“…This study shows that the typical dermoscopic features of BCC are usually present from the beginning of the natural history of this tumor. This is in contrast to what happens in small melanocytic lesions, in which fully represented melanoma‐specific criteria may be difficult to recognize. We found that 77% of small BCCs (≤5 mm diameter) could be diagnosed easily using the Menzies method.…”
Section: Commentsmentioning
confidence: 61%